THE IMPACT OF DIGITAL TRANSFORMATION ON THE FORMULATION OF NEW CORPORATE STRATEGIC DIRECTIONS - Kahrović, Ernad; Kahrović, Emina (International Journal of Economic Practice and Policy, 2022)
The digital economy, as an economy primarily functioning via digital technologies, has made its impact on the development of the digital transformation concept. Such a form of business transformation requires the integration of digital technologies in all industries. The paper underlines the importance of the essential elements of transformation, regarding customer experience, operational processes, business models, employee experience and digital platform, along with the key business spheres relating to competition, innovation and value, which digitalization changes on the way. The main goal of the paper, therefore, is to point to the impact of digital transformation on the process of formulating new corporate strategic directions. With this in mind, the paper’s main aim is to stress prospective corporate strategic directions of digital transformation under conditions of deep digital penetration. The paper is based on the working hypothesis that despite the fact that existing businesses most commonly start with market penetration, through developing a digital technology strategy, as well as a digital market expansion strategy, further development of digital transformation leads to the creation of digital platforms that are built by a mutual collaboration of numerous stakeholders connected through joint value creation and its delivery